CLINICAL APPLICATIONS OF GENOMIC DECODING IN PERSONALIZED PROACTIVE HEALTHCARE FOR CHRONIC NON-COMMUNICABLE DISEASES AND CANCER. (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize recent research on the role of genetics in chronic non-communicable diseases, with a particular focus on the nutrigenomics approach as a key strategy for proactive healthcare and effective prevention of prevalent conditions such as diabetes, cardiovascular disease, stroke, and cancer. Methods: A literature synthesis was conducted, analyzing recent research advancements in genetic testing, nutrigenomics, and their application in proactive healthcare. The study emphasizes findings relevant to the Vietnamese context, where implementation remains limited. Results: Advances in Next-Generation Sequencing and Artificial Intelligence have significantly reduced sequencing time and costs, enabling comprehensive genetic risk screening and lifestyle modification strategies. While these approaches are widely applied in developed nations, their utilization in Vietnam is still in its early stages. Key findings demonstrate the potential of nutrigenomics in assessing genetic predispositions and guiding personalized interventions for chronic diseases. Conclusion: Genomic decoding and nutrigenomics offer promising avenues for proactive and personalized healthcare in Vietnam. Addressing current challenges, including limited clinical implementation and population-specific genetic data, could facilitate the integration of genetic information into disease prevention strategies, ultimately improving health outcomes for chronic non-communicable diseases.
Keywords: Gene decoding; Nutrigenomics; Chronic non-communicable diseases; Proactive healthcare; Cancer